The effect of Islamic slaughter on food health based on Islamic texts - Soleimani, Saeed; Abdoljabari, Morteza; Karamkhani , Marzieh (Researcher Bulletin of Medical Sciences, 2021)
Objective: The issue of the philosophy of religious orders is a popular topic and the first book written in this regard is ‘Elal-o-Sharaye’ by Sheikh Sadough. The present study attempts to explain the effect religious texts have attributed to observing religious orders related to slaughter, which is referred to as ‘halal’ or healthy food in religious experts’ words. Of course, there is a relationship between being halal and food health, which is not within the scope of the present study. Materials and Methods: The method used in the present study was descriptive-analytical. Accordingly, interpretations and statements were used as sources based on the key words ‘physical health, Islamic slaughter, food health, halal, health from the perspective of Shari’a, the logic behind the divine decrees were investigated. In addition to describing the existing facts and collecting the required data based on the research questions, how and why slaughter is done in Islam and its different dimensions related to food health were explained from the perspective of Shari’a (in terms of being halal). Results: Scientific effects scientists attribute to Islamic slaughter have to do with theoretical reason. Definitely, theoretical reason cannot understand the criteria and the reasons behind religious orders independently of Shari’a in all cases, in the same was as considered by the holy Shari’a. Therefore, as long as there is no clear logic as the absolute or compelling reason for the effects of Islamic slaughter, all these issues are taken into account in the framework of the benefits of religious orders and they will not be more important than the effect attributed to Islamic slaughter in religious texts (becoming halal). Conclusion: The effect of Islamic slaughter, from the perspective of the religious expert, is certainly for the food to become halal and the meat to become healthy. Undoubtedly, the scientific effects of slaughter should be referred to as the logic behind religious decrees.